Efeitos da correção atmosférica em imagens Landsat 8 e diferentes modelos de radiação solar global na estimativa do saldo de radiação superficial - Pavão, Vagner Marques (2016)
The Pantanal and Mato Grosso Cerrado has experienced strong changes in land use and occupation over their territory. These changes, when performed on a large scale can change regional climate variables such as albedo, temperature and radiation balance. The radiation balance (Rn) is the difference between the radiation balance of the short-wave flows and long the Earth's surface and can be obtained in field measurements or by estimates from satellite images, such as the Landsat 8. However, one of the main drawbacks in this type of study is the effect of atmospheric scattering in radiance data recorded by the sensor. In this sense, the objective of this study was to evaluate the performance of the estimate of Rn with Landsat 8 images (with and without atmospheric correction) from solar radiation data (Rg) measured and estimated by different models in the Cerrado- Pantanal interface. The data used as input, as well as validation of the models were obtained by micrometeorological towers in Baía das Pedras (BPE), Farm Miranda (IMF) and experimental farm (FEX). All estimates Rg models suggested by Allen, were used (2007) and Zillman et al., (1972). In the Rn calculation were Landsat 8 reflectance letters downloaded at the top of the atmosphere (lane 10), subsequently corrected atmospherically and surface reflectance maps (band 2 to 7), which were estimated following parameters: albedo, vegetation indexes (NDVI, SAVI and LAI), surface temperature, longwave radiation emitted by the surface and end the radiation balance. In terms of local micrometeorology, all variables have seasonal variation, with the highest rainfall in the IMF and FEX and vapor pressure deficit equal at both sites. Already the air temperature and the variability of the albedo tended to be lower in BPE presented the highest Rg and Rn values. In general, the best estimates were obtained with instant Rn Rg measured data, followed by Allen model. Already the estimates of daily Rn were satisfactory and consistent with those seen in other studies in all experimental sites. So in terms of modeling of the instantaneous net radiation (Rn), data-based entries in Rg measured surface, where available, are given for best estimates of Rn. However, there is no Rg measured using equations such as Allen and Zillman used in this work, have satisfactory Rn estimates. However, these equations suggest the need for calibration region.